Prevention Behavior Among Family of Breast Cancer Patients - Pradanie, Retnayu; Ni’mah, Lailatun; Kusuma, Evi Nur Laili Rahma (International Journal of Psychosocial Rehabilitation, 2020)
Health screening, avoiding cigarette smoke, routine exercise, a healthy diet, adequate rest, and managing stress are included in a cancer prevention behavior program launched by the Ministry of Health of the Republic of Indonesia. Families of women patients with breast cancer are at greater risk of developing breast cancer and as such are expected to perform the behavior. The Health Belief Model Theory (HBM) is used to assess a person’s perception of performing health behaviors. This study aimed to analyze the factors related to breast cancer prevention behavior among families of women patients with breast cancer based on HBM. This research used a descriptive-analytic design with a cross-sectional approach. The independent variables were factors on HBM theory, while the dependent variable was cancer prevention behavior. Data collection used questionnaires with a sample size of 59 respondents. The samples were recruited using a total sampling technique. The data were analyzed using spearman-rho (α≤0.05). There was a relationship between perceived severity (p=0.012), perceived benefits (p=0.029), and perceived barrier with breast cancer prevention behavior in these women’s families (p=0.031). On the other hand, perceived susceptibility (p=0.388), perceived self-efficacy (p=0.064) and cues to action (p=0.054) were not correlated with breast cancer prevention behavior in female breast cancer patients’ families. These have to maintain their perceived severity, perceived benefits and perceived barriers, and improve their perceived susceptibility, perceived self-efficacy and cues to action to improve their breast cancer prevention.